2017
DOI: 10.1016/j.pbi.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-kingdom RNA trafficking and environmental RNAi for powerful innovative pre- and post-harvest plant protection

Abstract: Small RNA (sRNA)-induced RNA interference (RNAi) is an important conserved mechanism that modulates gene expression in almost all eukaryotes. Some sRNAs move short distances from cell to cell, while some travel long distances to spread systemically throughout the organism. Recent studies indicate that sRNAs can even move between organisms to induce gene silencing, a phenomenon called “cross-kingdom RNAi”. sRNA trafficking between a pathogen, pest, or symbiont and its respective host can have a significant impa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(83 citation statements)
references
References 81 publications
(132 reference statements)
1
77
0
5
Order By: Relevance
“…Based on studies of small RNA movement in plants and fungi described above, there are several pathways for cross‐kingdom small RNA transportation. Because naked small RNAs can move short and long distances in plants (Hyun et al , ) and can also be taken up by fungal cells (Wang, Thomas, and Jin, ), trafficking during plant–fungus interactions may involve naked small RNAs. For instance, when small RNAs targeting B. cinerea DCL1 and DCL2 genes were directly sprayed to Arabidopsis and tomato, treated plants gained resistance to grey mould disease, suggesting the naked exogenous small RNAs were assimilated into the pathogen and interfered with fungal virulence (Wang et al , ).…”
Section: Cross‐kingdom Trafficking Of Small Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on studies of small RNA movement in plants and fungi described above, there are several pathways for cross‐kingdom small RNA transportation. Because naked small RNAs can move short and long distances in plants (Hyun et al , ) and can also be taken up by fungal cells (Wang, Thomas, and Jin, ), trafficking during plant–fungus interactions may involve naked small RNAs. For instance, when small RNAs targeting B. cinerea DCL1 and DCL2 genes were directly sprayed to Arabidopsis and tomato, treated plants gained resistance to grey mould disease, suggesting the naked exogenous small RNAs were assimilated into the pathogen and interfered with fungal virulence (Wang et al , ).…”
Section: Cross‐kingdom Trafficking Of Small Rnasmentioning
confidence: 99%
“…Based on studies of small RNA movement in plants and fungi described above, there are several pathways for cross-kingdom small RNA transportation. Because naked small RNAs can move short and long distances in plants (Hyun et al, 2011) and can also be taken up by fungal cells (Wang, Thomas, and Jin, 2017) .…”
Section: Possible Pathways For Small Rna Crosskingdom Movementmentioning
confidence: 99%
“…During evolution, a certain balance between herbivores, their plant hosts and pathogens/parasites has been reached. Using RNAi as a gene manipulator, key herbivore genes involved in maintaining this homeostasis could be targeted . We define such RNAi as ‘RNAi plus ’.…”
Section: Synergy Of Rna With Plant Defense Chemicals and Micro‐organismsmentioning
confidence: 99%
“…In addition, the RNAi plus approach could also be integrated in current dsRNA delivery strategies. Small RNAs could move within an organism (systemic RNAi), from the environment to the organism (environmental RNAi) and between interacting organisms (cross‐species RNAi), thereby inducing gene silencing in the target organism . This cross‐species RNAi offers interesting delivery possibilities, using for example transgenic plants and micro‐organisms.…”
Section: Synergy Of Rna With Plant Defense Chemicals and Micro‐organismsmentioning
confidence: 99%
“…Consistent with the central role of dsRNA in triggering RNAi, numerous studies have shown that plants treated with virus‐specific dsRNA or single‐stranded RNA (ssRNA) molecules that fold into hairpin conformation showed antiviral resistance (Carbonell et al ., ; Gan et al ., ; Konakalla et al ., ; Tenllado and Diaz‐Ruiz, ; Tenllado et al ., ,b; Yin et al ., ). dsRNAs were also shown to be effective against fungi (Koch et al ., ; Wang et al ., , ) and insects (Baum et al ., ; Ghosh et al ., ; Li et al ., ; Luo et al ., ), thus providing important implications for dsRNA‐triggered RNAi as an emerging novel approach for crop protection. RNAi has been deployed for plant protection since it was discovered.…”
Section: Introductionmentioning
confidence: 99%